Exploration Of Parenting Practices In The Na Kanab Liana And Eu Nakfunu Traditions In The Boti Tribe - Benu, Eno Manekan; Bali, Engelbertus Nggalu; Margiani, Kristin; Kale, Sartika; Mundiarti, Vanida (Exploration in Early Childhood Research, 2024)
One of the highlights is the impressions of tradition in the lives of children as the smallest members of society. The impression of tradition can be seen from childcare practices before, during and after the tradition. Of the many interesting traditions that exist in the Boti community, there are two very unique traditions, namely the Na Kanab Liana tradition and the Eu Nakfunu tradition. This study aims to explore and describe the deeper meanings and values of the Na Kanab Liana tradition and the Eu Nakfunu tradition as well as childcare practices before, during and after the Na Kanab Liana tradition and the Eu Nakfunu tradition in the Boti community. Qualitative research methods were used using data collection techniques, in-depth interviews with 15 people (1 Boti Tribe leader, 1 traditional leader, 2 community leaders, 2 educational leaders and 9 parents), participatory observation, and analysis of other documentation that answered the research objectives. The results revealed that the Na Kanab Liana tradition and the Eu Nakfunu tradition hold high family values and togetherness in parenting. The parenting practices include experiential learning, careful monitoring of children, and early responsibility. In addition, both traditions also emphasize the importance of character building and life skills relevant to the environment in which they live. The implications of this research include a deeper understanding of the diversity of parenting practices across cultures, as well as the potential to enrich parenting practices that can be used in modern life.